Impact of Adjuvant Chemoradiotherapy for Rectal Cancer on the Long-Term Quality of Life and Late Side Effects: A Multicentric Clinical Evaluation by the Turkish Oncology Group - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2012)
Aim: Although preoperative chemoradiatherapy (CRT) has proven its benefits in terms of decreased toxicity, there is still a considerable amount of cases that do not receive postoperative CRT. Oncologists at different geographic locations still need to know the long-term effects of this treatment in order to manage patients successfully. The current paper reports on long-term quality of life (QOL) and late side effects after adjuvant CRT in rectal cancer patients from 5 centers in Anatolia. Methods: Rectal cancer patients treated with postoperative CRT with minimum 1-year follow-up and were in complete remission, were evaluated according to RTOG and LENT-SOMA scales. They were also asked to complete Turkish version of EORTC QLQ-C30 questionnaire and the CR-38 module. Each center participated with the required clinical data. Results: Two hundred and thirty patients with median age of 55 years participated and completed the study. Median follow-up time was 5 years. All patients received RT concomitant with chemotherapy. Common parameters that both increased functional health scales and yielded better symptom scores were long term interval after treatment and sphincter-saving surgery. In addition, surgery type and follow-up time were determined to be predictors of QOL scores and late toxicity grade. Conclusion: Postoperative CRT was found to have a great impact on the long term QOL and side effects in rectal cancer survivors. The factors that adversely affect these are abdominoperineal resection and shorter interval. The findings may encourage life-long follow-up and cooperation with patients, which should be mentioned during the initial counseling.
Keywords: Rectal cancer; chemoradiotherapy; quality of life; Anatolia; ACUTE GASTROINTESTINAL COMPLICATIONS; SULFASALAZINE; RESECTION; WOMEN